2017
DOI: 10.1038/srep39789
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped Carbon Derived from ZIF-8 as a High-performance Metal-free Catalyst for Acetylene Hydrochlorination

Abstract: Acetylene hydrochlorination is a major industrial technology for manufacturing vinyl chloride monomer in regions with abundant coal resources; however, it is plagued by the use of mercury(II) chloride catalyst. The development of a nonmercury catalyst has been extensively explored. Herein, we report a N-doped carbon catalyst derived from ZIF-8 with both high activity and quite good stability. The acetylene conversion reached 92% and decreased slightly during a 200 h test at 220 °C and atmospheric pressure. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 25 publications
9
50
1
1
Order By: Relevance
“…Still, carbon materials, including defect‐rich carbons, graphitic carbon nitride, and heteroatom‐doped carbons ( i. e ., N, P, B, S) are highly desirable alternatives, owing to their significant environmental and cost advantages compared to metal‐based catalysts . In particular, nitrogen‐doped carbons (NCs), derived via carbonization of C/N‐precursors ( i. e ., polyaniline, polydopamine, ZIF‐8), stand out as the most promising candidates, rivaling the initial activity of their metal‐based analogues at elevated reaction temperatures . Despite these encouraging results, the applicability of NCs is hindered by their insufficient durability under relevant process conditions ( T =403‐453 K, P =1.5 bar, HCl : C 2 H 2 =1.1 : 1) .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Still, carbon materials, including defect‐rich carbons, graphitic carbon nitride, and heteroatom‐doped carbons ( i. e ., N, P, B, S) are highly desirable alternatives, owing to their significant environmental and cost advantages compared to metal‐based catalysts . In particular, nitrogen‐doped carbons (NCs), derived via carbonization of C/N‐precursors ( i. e ., polyaniline, polydopamine, ZIF‐8), stand out as the most promising candidates, rivaling the initial activity of their metal‐based analogues at elevated reaction temperatures . Despite these encouraging results, the applicability of NCs is hindered by their insufficient durability under relevant process conditions ( T =403‐453 K, P =1.5 bar, HCl : C 2 H 2 =1.1 : 1) .…”
Section: Figurementioning
confidence: 99%
“…In particular, nitrogen‐doped carbons (NCs), derived via carbonization of C/N‐precursors ( i. e ., polyaniline, polydopamine, ZIF‐8), stand out as the most promising candidates, rivaling the initial activity of their metal‐based analogues at elevated reaction temperatures . Despite these encouraging results, the applicability of NCs is hindered by their insufficient durability under relevant process conditions ( T =403‐453 K, P =1.5 bar, HCl : C 2 H 2 =1.1 : 1) . In particular, pore blockage through the formation of carbonaceous residues has been identified as the major reason for catalyst deactivation .…”
Section: Figurementioning
confidence: 99%
“…In previous studies of numerous metal chlorides and carbon catalytic materials,, activated carbon‐supported AuCl 3 catalyst (AuCl 3 /AC) as a green and efficient non‐mercury catalyst is considered to be most promising alternative to HgCl 2 /AC catalyst for acetylene hydrochlorination ,. Compared with HgCl 2 /AC catalyst, AuCl 3 /AC catalyst exhibits better initial activity.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed from Figure (a) that the acetylene conversions for all the catalysts increased at first and then tended to be stable after about 6 h of reaction. ZIF‐8C (no Co present in the catalyst), the reference sample, leads to an acetylene conversion of 54%, which is close to the result in our previous report . As a small amount of Co was introduced to the carbon catalysts, their catalytic activities improved significantly.…”
Section: Resultsmentioning
confidence: 96%
“…Dai and co‐workers synthesized several N‐doped carbons with different dopants, finding that these materials all presented better catalytic activity than the undoped sample . Our group developed a N‐doped porous carbon catalyst derived from zeolitic imidazolate framework (ZIF)‐8 (a metal–organic framework material) giving considerable and stable acetylene conversion, and experimental results and theoretical calculation demonstrated that carbon atoms adjacent to the pyridinic nitrogen are the active sites . In the latest studies, the co‐doping strategy was utilized to further improve the catalytic performance of carbon catalysts for acetylene hydrochlorination.…”
Section: Introductionmentioning
confidence: 99%